Tumour budding is a novel marker in breast cancer: the clinical application and future prospects - Huang, Ting; Bao, Hui; Meng, Yu-hua; Zhu, Jian-lin; Chu, Xiao-dong; Chu, Xiao-li; Pan, Jing-hua (Annals of medicine (Helsinki), 2022)
Breast cancer (BC) is a group of markedly heterogeneous tumours. There are many subtypes with different biological behaviours and clinicopathological characteristics, leading to significantly different prognosis. Despite significant advances in the treatment of BC, early metastatic is a critical factor for poor prognosis in BC patients. Tumour budding (TB) is considered as the first step process of tumour metastasis and is related to the epithelial-mesenchymal transition (EMT). TB has been observed in a variety of cancers, such as colorectal and gastric cancer, and had been considered as a distinct clinicopathological characteristics for early metastasis. However, TB evaluation standards and clinical application are not uniform in BC, as well as its molecular mechanism is not fully understood. Here, we reviewed the interpretation criteria, mechanism, clinicopathological characteristics and clinical application prospects of TB in BC. Key messages Currently, tumour budding is a poor prognosis for various solid tumours, also in breast cancer. Tumour budding is based on epithelial-mesenchymal transition and tumour microenvironment factors and is presumed to be an early step in the metastatic process. Breast cancer tumour budding still needs multi-centre experiments. We summarize the current research on breast cancer tumour budding, analyse the method of discriminating breast cancer tumour budding and explore the prognostic role and mechanism in breast cancer.